2018
DOI: 10.3390/ijerph15010059
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Uptake, Toxicity, Detoxification, and Speciation in Plants: Physiological, Biochemical, and Molecular Aspects

Abstract: Environmental contamination with arsenic (As) is a global environmental, agricultural and health issue due to the highly toxic and carcinogenic nature of As. Exposure of plants to As, even at very low concentration, can cause many morphological, physiological, and biochemical changes. The recent research on As in the soil-plant system indicates that As toxicity to plants varies with its speciation in plants (e.g., arsenite, As(III); arsenate, As(V)), with the type of plant species, and with other soil factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
280
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(296 citation statements)
references
References 361 publications
(651 reference statements)
10
280
0
6
Order By: Relevance
“…Furthermore, in our previous study, the content of H2O2 was also observed to enhance in the shoots and roots of barley seedlings under DBP stress (Kumari et al 2019). The accumulation of H2O2 might be because of photorespiratory oxidation or β-oxidation induced by the exposure to DBP (Abbas et al 2018).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, in our previous study, the content of H2O2 was also observed to enhance in the shoots and roots of barley seedlings under DBP stress (Kumari et al 2019). The accumulation of H2O2 might be because of photorespiratory oxidation or β-oxidation induced by the exposure to DBP (Abbas et al 2018).…”
Section: Discussionmentioning
confidence: 71%
“…In wheat plants under DEHP exposure, the activity of APX increases as compared to the control (Gao et al 2018). APX catalyzes the reduction of H2O2 using ascorbate as an electron donor; it plays an important role in the mitigation of intracellular ROS content (Abbas et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…15 Q10SX6) was overexpressed only in the sample from Malus sylvestris pollen. Arsenate reductase protein is required for arsenate resistance (Abbas et al, 2018). It was shown that absence of arsenic reductase in Arabidopsis results in accumulation of arsenic 10-to 16-fold more compared with wild-type plants and this can lead to toxic effects on pollen tube development (Dhankher et al, 2006).…”
Section: Protein Three-dimensional (3-d) Visualization and Descriptiomentioning
confidence: 99%
“…Antioxidant defence system: Under As stress, plants can induce oxidative stress, which causes an imbalance between ROS generation and ROS scavenging. (Abbas et al, 2018). Among the antioxidant enzymes, SOD is a major enzyme that constitutes the first line of defence against ROS in plants ( Abbas et al, 2014).…”
Section: Proline Accumulationmentioning
confidence: 99%